2017
DOI: 10.1016/j.jiph.2016.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice about malaria in south-western Saudi Arabia: A household-based cross-sectional survey

Abstract: This study aimed to assess the level of knowledge, attitudes, and practices (KAP) concerning malaria and malaria prevention among rural populations residing in the southwestern region of Saudi Arabia. This was a household-based cross-sectional survey, using structured questionnaire that was developed and distributed among households selected randomly from 19 villages (clusters) located in a southwestern region of Saudi Arabia, north of the border with Yemen. The data collected were analyzed using SPSS version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 7 publications
6
29
4
2
Order By: Relevance
“…The main types of malaria preventive measures frequently reported by the present study participants were use of mosquito net, drain stagnated water (mosquito breeding sites), house spray (DDT) and fumigation. This finding was consistence with previous studies from other part of Ethiopia, Tanzania, India, and Saudi Arabia [21,35,36,37]. In this study, (85.5%) respondents knew that mosquito nets prevent malaria, and hence made use of them to prevent the disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The main types of malaria preventive measures frequently reported by the present study participants were use of mosquito net, drain stagnated water (mosquito breeding sites), house spray (DDT) and fumigation. This finding was consistence with previous studies from other part of Ethiopia, Tanzania, India, and Saudi Arabia [21,35,36,37]. In this study, (85.5%) respondents knew that mosquito nets prevent malaria, and hence made use of them to prevent the disease.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, more than 85% of respondents believed that malaria is preventable disease which is higher than the finding of a study in south-western Saudi Arabia (30.2%) [35]. The main types of malaria preventive measures frequently reported by the present study participants were use of mosquito net, drain stagnated water (mosquito breeding sites), house spray (DDT) and fumigation.…”
Section: Discussioncontrasting
confidence: 77%
“…7 Similarly, in studies in Saudi Arabia, where knowledge of this disease is acceptable, there is a gap between knowledge and prevention-related practices, which require innovative strategies based on local experiences and evidence to promote and encourage the community to adopt effective control and protection measures. 8 We found that the community of Vistahermosa presented a low level of knowledge of the Anopheles mosquito, which is the malaria vector, as well as the vector control forms. Many people confused the vector of malaria with the vector of dengue, chikungunya and zika (Aedes spp.…”
Section: Discussionmentioning
confidence: 78%
“…In the pre-intervention phase, the total KAP scores for students group (mean rank = 166·6) and non-students group (mean rank = 235·1) were statistically significantly different and displayed a median of 12 (IQR = 9·5-14) in students group and 14 (IQR = 11-17) in non-students group, respectively. In the post-intervention phase, the total KAP scores for students group (mean rank = 176·4) and non-students group (mean rank = 167·1) were not statistically significantly different and displayed a median of 17 (IQR = [15][16][17][18][19] in students group and 17 (IQR = 13-19) in nonstudents group, respectively. Based on these results, it can be assumed that the intervention programme had a better effect on students group.…”
Section: Impact Of the Intervention Programme On Kap Of Students And mentioning
confidence: 94%
“…We assessed KAP of respondents regarding SFTS based on their responses to the questionnaire provided. Table 2 shows the median (IQR) of KAP and total KAP score was 3 (1-5), 8 (6·5-9), 3 (2-3) and 13 (11)(12)(13)(14)(15)(16)(17) in the pre-invention phase and 5 (3-7), 10 (7-10), 3 (3-3) and 17 (14)(15)(16)(17)(18)(19) in the post-invention phase, respectively. The results indicated that there was a significant increase in the four type scores (Ps < 0·001).…”
Section: Impact Of the Intervention Programme On Knowledgementioning
confidence: 99%